2006
DOI: 10.1029/2005jd006899
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the distribution of the volcanic aerosol cloud from the 1783–1784 Laki eruption

Abstract: [1] We conducted simulations of the atmospheric transformation and transport of the emissions of the 1783-1784 Laki basaltic flood lava eruption (64.10°N, 17.15°W) using the NASA Goddard Institute for Space Studies modelE climate model coupled to a sulfur cycle chemistry model. The model simulations successfully reproduced the aerosol clouds of the 1912 Katmai and 1991 Mount Pinatubo eruptions, giving us confidence in the Laki simulations. Simulations of the Laki eruption produce peak zonal mean sulfate (SO 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
200
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(223 citation statements)
references
References 58 publications
20
200
3
Order By: Relevance
“…Following the Greenland-to-Antarctica sulfate flux ratios, the simulated AODs for both eruptions are stronger in the NH than in the Southern Hemisphere (SH). The aerosol load for the simulated 536 event is largely constrained to the NH, with the largest AOD found north of 30°N, similar to previous model simulations (Oman et al 2006) and satellite observations (Bourassa et al 2010) of other high-latitude eruptions. It is also consistent with the distribution of historical observations of diminished solar intensity in 536 CE, with the most reliably located accounts originating from Rome (42°N) and Constantinople (41°N), but a noted lack of direct observations documented by scholars residing at lower latitudes (Arjava 2005).…”
Section: Radiative Forcingsupporting
confidence: 65%
“…Following the Greenland-to-Antarctica sulfate flux ratios, the simulated AODs for both eruptions are stronger in the NH than in the Southern Hemisphere (SH). The aerosol load for the simulated 536 event is largely constrained to the NH, with the largest AOD found north of 30°N, similar to previous model simulations (Oman et al 2006) and satellite observations (Bourassa et al 2010) of other high-latitude eruptions. It is also consistent with the distribution of historical observations of diminished solar intensity in 536 CE, with the most reliably located accounts originating from Rome (42°N) and Constantinople (41°N), but a noted lack of direct observations documented by scholars residing at lower latitudes (Arjava 2005).…”
Section: Radiative Forcingsupporting
confidence: 65%
“…Larsen, 1979Larsen, , 2000Thordarson and Self, 1993, 1998Self et al, 1996Self et al, , 1997Thordarson et al, , 2003aKeszthelyi et al, 2000Keszthelyi et al, , 2004Guilbaud et al, 2005). It has also demonstrated that over the last 1130 years, these events are the most significant of Icelandic eruptions in terms of environmental and climatic effects because of the huge amount of sulphur (100-250 Mt of SO 2 ) they release into the atmosphere (Thorarinsson, 1979;Metrich et al, 1991;Stothers, 1996Stothers, , 1998Thordarson et al, , 2001Thordarson et al, , 2003bOman et al, 2006) The high-discharge flood lava events are prolonged fissure eruptions that last for months to years and feature numerous eruption episodes (Fig. 9).…”
Section: Effusive Eruptionsmentioning
confidence: 99%
“…The Laki flood lava eruption in 1783-1784 took place on a 27 km long continuous volcanic fissure in the ice-free part of the Grímsvötn system and produced about 14.7 km 3 of lava, covering an area of about 565 km 2 , and about 0.4 km 3 (DRE) of tephra (Thordarson and Self, 1993). The Laki eruption released about 120 Mt of SO 2 into the atmosphere, producing an aerosol cloud that covered the top northern quarter of the globe and produced significant environmental and climatic effects Chenet et al, 2005;Oman et al, 2006). All other historical eruptions took place on the ice-covered part of the system.…”
Section: Grímsvötn Volcanic Systemmentioning
confidence: 99%
“…Another approach, which potentially could shed light on the physical mechanisms governing the development of volcanic plumes and help to resolve some of the problems, is based on GCM simulations interactively accounting for the development of the stratospheric volcanic aerosol layer [45][46][47][48][49][50]. p0075 Timmreck et al [49], Oman et al [48] and Aquila et al [45] used so-called 'bulk' aerosol models when they calculated SO 2 to sulphate conversion and tracked their bulk concentration.…”
Section: P0065mentioning
confidence: 99%
“…p0075 Timmreck et al [49], Oman et al [48] and Aquila et al [45] used so-called 'bulk' aerosol models when they calculated SO 2 to sulphate conversion and tracked their bulk concentration. The aerosol size distributions were prescribed and optical properties were precalculated.…”
Section: P0065mentioning
confidence: 99%